2019
DOI: 10.1080/1359432x.2019.1642874
|View full text |Cite
|
Sign up to set email alerts
|

Levels of workplace bullying and escalation – a new conceptual model based on cut-off scores, frequency and self-labelled victimization

Abstract: The aim of this study was to identity levels of workplace bullying based on cut-off scores, frequency and self-labelled victimization, and to use these levels to identify the escalation of workplace bullying in terms of onset of different negative acts. Data were collected from a representative sample of the Swedish workforce (n = 1856). Bullying was measured using the Negative Acts Questionnaire-Revised together with self-labelled victimization based on a definition. Other variables included aspects of work e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 40 publications
1
53
0
1
Order By: Relevance
“…In our sample, the range was from 22 to 66. According to the definition of workplace bullying, as well as, suggestions of cut-off scores (Notelaers and Einarsen 2013) and levels of bullying (Rosander and Blomberg 2019), this means that many were exposed to bullying behaviours, but not all were bullied. When referring to workplace bullying of just "bullying" onwards we mean an exposure to bullying behaviours without categorizing any individual result as being workplace bullying or not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, the range was from 22 to 66. According to the definition of workplace bullying, as well as, suggestions of cut-off scores (Notelaers and Einarsen 2013) and levels of bullying (Rosander and Blomberg 2019), this means that many were exposed to bullying behaviours, but not all were bullied. When referring to workplace bullying of just "bullying" onwards we mean an exposure to bullying behaviours without categorizing any individual result as being workplace bullying or not.…”
Section: Methodsmentioning
confidence: 99%
“…Notelaers and Einarsen (2013) proposed two cut-off scores for determining how to interpret frequency and amount of exposure in relation to workplace bullying. Rosander and Blomberg (2019) suggested levels of bullying where exposure over the lower cut-off together with a lower frequency was framed as the risk of bullying. However, they showed that already when categorized as in risk of bullying the consequences for the experience of work, and one's health were distinct compared to the not bullied.…”
Section: Introductionmentioning
confidence: 99%
“…The specific negative acts covered by the behavioural experience method may, of course, also be construed differently. Also, aspects such as ability to defend oneself if exposed is not normally part of the measure when using this method, although Rosander and Blomberg (2019) suggested a measure for that as an addition to the behavioural experience method. In all, each method has shortcomings which would speak for using a combination of both methods when studying bullying and gender.…”
Section: Gender Differences In Workplace Bullyingmentioning
confidence: 99%
“…In terms of criteria for bullying, and of discrepancies in exposure to bullying behaviours and self-labelling, Vie et al (2011) showed that there are negative consequences of exposure to bullying behaviours regardless if it is labelled as bullying or not. Rosander and Blomberg (2019) showed that already those in risk of being bullied, that is, people that are not exposed on a weekly basis and do not self-label as bullied, but still are the target of a number of negative acts at least now and then, report more health and mental health problems than those who are not bullied.…”
Section: Gender Differences In Consequences Of Workplace Bullyingmentioning
confidence: 99%
See 1 more Smart Citation